2021
DOI: 10.1017/jfm.2020.1121
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the acceleration statistics and added-mass force of deformable bubbles in intense turbulence

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Salibindla et al have shown that the added mass coefficient for deformable bubbles decreases as the bubbles deform and their aspect ratio along their semi-major and minor axes increases. 53 Sangani et al have illustrated that the changes in the added mass of the bubbles as a function of their surface tension (or Capillary number) are very small and negligible. 54 Presas et al have also mentioned that the added mass generally increases as the surface of the particle becomes more rigid.…”
Section: Methodsmentioning
confidence: 99%
“…Salibindla et al have shown that the added mass coefficient for deformable bubbles decreases as the bubbles deform and their aspect ratio along their semi-major and minor axes increases. 53 Sangani et al have illustrated that the changes in the added mass of the bubbles as a function of their surface tension (or Capillary number) are very small and negligible. 54 Presas et al have also mentioned that the added mass generally increases as the surface of the particle becomes more rigid.…”
Section: Methodsmentioning
confidence: 99%
“…( 6). The equation of motion for isolated deformable non-spherical bubbles is given by Salibindla et al (2021):…”
Section: Relevant Equationsmentioning
confidence: 99%
“…where the six terms on the right-hand side represent addedmass, drag, pressure gradient, history, lift and buoyancy forces, respectively. The added mass coefficient is C A , and ∇P is the pressure gradient around the bubble Salibindla et al (2021).…”
Section: Relevant Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In EFD methods, researchers have developed numerous experimental techniques to study added mass, such as free oscillation [8][9][10][11] and forced oscillation [12][13][14][15][16]; these inertia methods, with extensive experimental setups like the Rotating Arm (RA) and Planar Motion Mechanism (PMM), are being developed [17,18]. Most added masses are currently analyzed from the hydrodynamic characteristics of oscillation, but new methods for solving added mass, such as PIV testing and trajectory tracking, have emerged [19][20][21], which can solve the added mass of deformable objects. EFD methods are the most direct way to solve added mass, with relatively mature related technologies.…”
Section: Introductionmentioning
confidence: 99%